2017
DOI: 10.1002/biof.1358
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of phloretin and its glycosylated derivative on rotenone‐induced toxicity in human SH‐SY5Y neuronal‐like cells

Abstract: Phloretin and phlorizin are the two strong natural antioxidants whose biological and pharmacological applications are rapidly growing in different human pathological conditions. The neuroprotective activity of the two flavonoids has been analyzed on cell culture of neuroblastoma cells. The neuroprotective activity of the two flavonoids has been analyzed on cell culture of neuroblastoma cells and evaluated by testing cell vitality, mitochondrial transmembrane potential and ROS production, antioxidant enzymes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 46 publications
3
27
0
1
Order By: Relevance
“…In addition, the present study demonstrated that phlorizin attenuates the DNA damage, cells apoptosis, and necrosis induced by H 2 O 2 in HepG2 cells ( p < .05). These results were consistent with that in previous study showed that phlorizin attenuates the DNA damage and apoptosis in rotenone‐induced SH‐SY5Y cells (Barreca et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the present study demonstrated that phlorizin attenuates the DNA damage, cells apoptosis, and necrosis induced by H 2 O 2 in HepG2 cells ( p < .05). These results were consistent with that in previous study showed that phlorizin attenuates the DNA damage and apoptosis in rotenone‐induced SH‐SY5Y cells (Barreca et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…LDH activity in the medium was determined using a commercially available kit from BioSystems S. A and expressed in function of the total amount of the enzyme present in the control (cells without t‐BOOH) released after an induced total cell lysis by sonication. Caspase 3 activation and quantification of protein carbonyl groups were performed according to the method described by Barreca et al () and Bellocco et al (). Cactus pear extracts, at concentration tested, did not show any interference with the assays performed.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, the dielectric properties of the blood change, and in particular, the partial polarization vectors associated with each anomalous phenomenon (disease) can change. It may be useful to study the dielectric properties of blood related to neurodegenerative diseases and the protective effects of some natural compounds [14][15][16][17][18]. Obviously, the investigation of these pathologies is very difficult if it is carried out by considering partial polarization directly, since a direct measure of them is very difficult.…”
Section: Introductionmentioning
confidence: 99%